Adsorptive Removal of Benzene and Toluene from Aqueous Environments by Cupric Oxide Nanoparticles: Kinetics and Isotherm Studies - Leili Mohammadi; Edris Bazrafshan; Meissam Noroozifar; Alireza Ansari-Moghaddam; Farahnaz Barahuie; Davoud Balarak (Journal of Chemistry)
Removal of benzene and toluene, as the major pollutants of water resources, has attracted researchers’ attention, given the risk they pose to human health. In the present study, the potential of copper oxide nanoparticles (CuO-NPs) in eliminating benzene and toluene from a mixed aqueous solution was evaluated. For this, we performed batch experiments to investigate the effect of solution pH (3–13), dose of CuO-NPs (0.1–0.8 g), contact time (5–120 min), and concentration of benzene and toluene (10–200 mg/l) on sorption efficiency. The maximum removal was observed at neutral pH. By using the Langmuir model, we measured the highest adsorption capacity to be 100.24 mg/g for benzene and 111.31 mg/g for toluene. Under optimal conditions, adsorption efficiency was 98.7% and 92.5% for benzene and toluene, respectively. The sorption data by CuO-NPs well fitted into the following models: Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich model. The experimental information well fitted in the Freundlich for benzene and Langmuir for toluene. Based on the results, adsorption followed pseudo-second-order kinetics with acceptable coefficients. The findings introduced CuO-NPs as efficient compounds in pollutants adsorption. In fact, they could be used to develop a simple and efficient pollutant removal method from aqueous solutions.